2023
DOI: 10.1029/2022jb026075
|View full text |Cite
|
Sign up to set email alerts
|

Subduction‐Induced Asthenospheric Flow Around the Songliao Basin in NE China Revealed by Shear Wave Splitting Measurements of Dense Seismic Arrays

Abstract: When applied to plate boundaries such as midocean ridges and subduction zones, plate tectonics theory has satisfactorily explained the genesis of volcanism (Morgan, 1968). However, this hypothesis does not provide a satisfactory explanation for intraplate volcanism, which occurs far from plate boundaries (Lee & Grand, 2012). Intraplate volcanism is conventionally attributed to deep-rooted mantle plumes that originate at the core-mantle boundary (Morgan, 1971), such as the Hawaii volcanic chain, whereas the man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 86 publications
0
3
0
Order By: Relevance
“…Xu et al. (2023) detected anisotropy beneath the Songliao Basin, displaying a circular distribution in the fast direction. They linked this observation to a persistent high‐velocity anomaly in the upper mantle, indicating early lithospheric subsidence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Xu et al. (2023) detected anisotropy beneath the Songliao Basin, displaying a circular distribution in the fast direction. They linked this observation to a persistent high‐velocity anomaly in the upper mantle, indicating early lithospheric subsidence.…”
Section: Discussionmentioning
confidence: 99%
“…obtained inversion results showing fast Vs at depths of approximately 40-100 km and suggested that the dense mantle lid beneath the Songliao Basin might hinder the migration of asthenospheric melt to the surface Xu et al (2023). detected anisotropy beneath the Songliao Basin, displaying a circular distribution in the fast direction.…”
mentioning
confidence: 81%
“…Previous studies investigated the crustal and upper mantle structures to better understand the lithosphere formation and modification across the northern segment of the Tanlu fault zone. The seismic azimuth anisotropy showed that the fast directions within the northern segment of the Tanlu fault zone were systematically shifted to NW-SE, which may reflect the extension of the lithosphere since the late Mesozoic [20][21][22][23] . A deep seismic reflection profile in the northern region of the Dunhua-Mishan fault within the Jiamusi-Mudanjiang block revealed that the Dunhua-Mishan Fault penetrate the crust into the upper mantle 24 .…”
mentioning
confidence: 99%